Sequence-specific covalent labelling of DNA. (22nd March 2011) - Gottfried, Anna; Weinhold, Elmar
Abstract : Sequence-specific DNA modification is of significance for applications in bio- and nano-technology, medical diagnostics and fundamental life sciences research. Preferentially, labelling should be performed covalently, which avoids doubts about label dissociation from the DNA under various conditions. Several methods to label native DNA have been developed in the last two decades. Triple-helix-forming oligodeoxynucleotides and hairpin polyamides that bind DNA sequences specifically in the major and minor groove respectively were used as targeting devices for subsequent covalent labelling. In addition, enzyme-directed labelling approaches utilizing nicking endonucleases in combination with DNA polymerases or DNA methyltransferases have been employed. This review summarizes various techniques useful for functionalization of long native DNA.